2012
DOI: 10.1109/lpt.2012.2196427
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Delivery of Integrated Wired and Wireless Services in UDWDM-RoF-PON Coherent Access Network

Abstract: A high-capacity coherent ultradense wavelengthdivision multiplexing passive optical network integrated with a 60-GHz radio-over-fiber system has been designed and experimentally demonstrated for the first time. In this proposed architecture, millimeter-wave signal generation is achieved by coherent technology, in place of the optical carrier suppression technique, which requires modulators with large bandwidth and precise optical interleavers. The system fully exploits advantages of coherent access networks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Compared with previous studies [5][6][7][8][9][10][11], the proposed scheme has such merits. First, in a hybrid ONU (HONU), alternative access is realized only with a PC, polarization stabilizer, and polarization beam splitter (PBS) instead of the optical filters or interleaves (ILs) usually used in conventional schemes.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Compared with previous studies [5][6][7][8][9][10][11], the proposed scheme has such merits. First, in a hybrid ONU (HONU), alternative access is realized only with a PC, polarization stabilizer, and polarization beam splitter (PBS) instead of the optical filters or interleaves (ILs) usually used in conventional schemes.…”
Section: Introductionmentioning
confidence: 91%
“…In [10], a tunable laser is used to provide a coherent optical local oscillator (LO) for homo-/heterodyne beating to coherently down-convert the optical signal to the baseband electrical one for wired access or to the mm-wave one for wireless access according to the requirement of the user terminals. The authors of [11] proposed a novel coherent access network architecture that integrates ROF with ultradense-WDM-PON (UDWDM-PON) to simultaneously provide both multi-gigabit wired and wireless services. This scheme can realize alternative wired and wireless access, but the laser sources in the optical network unit (ONU) make the system complex.…”
Section: Introductionmentioning
confidence: 99%
“…This has attracted significant amount of interests from both the industry and academics [3,12,26]. The current research for hybrid wiredwireless networks mainly focus on some basic characters, e.g., the integrated approach of between the wired and wireless networks [7], networked performance analysis [13,38], and so on. Few research results has been reported on H 2 /H ∞ filtering for hybrid wired-wireless networked systems.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve the generation of a photonic microwave signal with more spectral-efficient vector modulation, the optical-assisted microwave-mixing device described in Fig. 1(b) has been proposed and adopted extensively in the recently reported high-capacity RoF links [3][4][5][6][7][8][9]. In this method, one of the OCs provided by the photonic microwave source is filtered out and mixed with the data via the EOM.…”
mentioning
confidence: 99%
“…The random phase fluctuation between the OCs induces very large noise in the generated microwave [10]. Even though the complicated phase-estimation algorithm (PEA) based on digital-signal processing (DSP) has already been carried out to remedy this defect in the RBSs [4][5][6][7][8][9], the transmission performance of the RoF system is still difficult to improve remarkably. Moreover, the complicated DPS component used in coherent core transport networks is unsuitable for RoF-based optical and wireless access networks considering the cost and power consumption.…”
mentioning
confidence: 99%